Hayek and Schmitt on the "depoliticization" of the economy - Daniel Nientiedt (Duke University, Center for the History of Political Economy (CHOPE), 2022)
Both Friedrich Hayek and Carl Schmitt are critical of the role of economic interest groups in modern democracies. This paper begins by comparing their descriptions of how such groups attempt to obtain favorable treatment from the state ('rent seeking'). The paper then discusses the proposed solutions. Schmitt's solution, called depoliticization, involves the establishment of an authoritarian state with a corporatist economic system. Hayek, by contrast, argues in favor of limiting the ability of politicians to grant privileges to economic groups. The paper finally asks whether, as claimed in the literature, Hayek's solution is similar to Schmitt's in that both attempt to shield the free market economy from democratic oversight. It is argued that Hayek's solution is not undemocratic (unless one defines democracy as pure majoritarianism), while Schmitt's solution is not conducive to free markets.
Keywords: 330